Biodisinfestation With Agricultural By-Products Developed Long-Term Suppressive Soils Against Meloidogyne incognita in Lettuce Crop - Gandariasbeitia, Maite; López-Pérez, José Antonio; Juaristi, Berdaitz; Abaunza, Leire; Larregla, Santiago (Frontiers in Sustainable Food Systems, 2021)
Soil biodisinfestation is the process generated after the incorporation of organic amendments followed by a plastic cover during warm seasons to control soilborne diseases. Among organic amendments, the use of agricultural by-products could be an interesting alternative as it promotes circular economy. In this study, beer bagasse and defatted rapeseed cake together with fresh cow manure were incorporated into the soil (1.5, 0.5 and 20kg/m2, fresh weight, respectively) to assess their capacity to reduce disease incidence caused by the root-knot nematode Meloidogyne incognita in protected lettuce crops and develop suppressive soils. The trial was conducted in a poly-tunnel for seven weeks during which temperature was continuously recorded at three different soil depths (15, 30 and 45cm). Short- and long-term effects were assessed: before treatment, after treatment, after first crop post-treatment and one year post-treatment. Disease incidence and changes in nematode community structure were analyzed along with microbiological properties and general physicochemical parameters. After biodisinfestation, microbiological activity significantly increased in the treated soils and changes in the nematode community structure were detected in detriment of M. incognita and other plant-parasitic nematodes. These effects were more apparent after the first crop post-treatment than right after biodisinfestation. In the first crop after biodisinfestation, lettuce yield increased in the treated plots and galling indices were significantly lower. One year after treatment, differences between treatments could be observed in the incidence of the damage caused by M. incognita that remained lower in the treated plots. In this trial, the addition of beer bagasse and rapeseed cake along with fresh manure in biodisinfestation treatment demonstrated nematicidal effects against M. incognita. Moreover, we suggest that the compounds released during the degradation of these by-products and the sub-lethal temperatures achieved in this trial during biodisinfestation (<42°C) were the key to develop suppressive soils in the long-term.